Fabric Coated with Shape Memory Polyurethane and Its Properties - Jahid, Md Anwar (Polymers (Basel), 2018)
In order to provide thermo-physiological comfort to the wearer, textile materials should have some functional property like water-resistance or water vapor transmission (WVT), so that perspiration can evaporate and be transmitted from the body surface to the environment even in extreme weather conditions that require wind and rain proof. Shape memory polyurethane (SMPU) could possibly be a candidate; it is a functional textile material that meets such requirements. In this research, we synthesized a series of SMPUs, which are responsive materials, to test whether these coated cotton fabrics could provide thermal insulation with lower permeability at low temperature or low relative humidity (RH), and high permeability at room temperature or above, or high relative humidity with its water-resistance property. In this paper, we have proposed a segmented shape memory polyurethane for coated textiles in order to have a water-resistant textile with good water vapor transmitting ability.